PERANCANGAN SOFT STARTING PADA MOTOR INDUKSI SATU FASA - Muhammad Zaki; Nurhazizah Nurhazizah; Zanu Saputra; Yudhi Yudhi (Politeknik Manufaktur Negeri Bangka Belitung, 2021)
Induction motors have a problem that is very detrimental to the system, namely their high starting current when turned on directly. Efforts to reduce the large initial currents required a soft starting method. Soft Starting aims to get a low starting current and a smoother motor rotation. The Soft Starting method will regulate the voltage and current into the induction motor by providing a triggering angle on the TRIAC which is regulated by the Arduino platform by applying the Fuzzy Logic control system. This Fuzzy Logic method uses one input